Risk Analysis as a Factor Affecting the Performance of Sharia Commercial Banks - Laely Aghe Africa; Titis Puspitaningrum D.K (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: This study aims to analyze the factors that influence the performance of sharia commercial banks by using Return on Assets (ROA) and Return on Equity (ROE) as dependent variables. The independent variables used are Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), profit-sharing financing and derivative liabilities which are proxies of risk analysis. The sample used is 63 sharia commercial bank financial statements for the period 2016-2020. Design/methodology/approach: This study uses quantitative method and multiple regression analysis with SPSS Version 25 Findings: The results of this study indicate that the variables of NPF, profit-sharing financing and derivative liabilities have an effect on ROA. Meanwhile, the variables that affect ROE are only NPF and derivative liabilities. Research limitations/implications: This research is expected to be a guideline for management and other stakeholders in considering the results of banking performance as measured by ROA and ROE by looking at credit risk analysis as measured by NPF, FDR, profit-sharing financing, and derivative liabilities. These considerations are expected to have a good effect on attracting depositors and convincing them to invest their funds. The financial reports that have been prepared are then reported to Bank Indonesia and shareholders in order to increase transparency in the eyes of stakeholders. Practical implications: Research conducted on sharia commercial banks shows good results for the bank management and other stakeholders. There are several things that need to be considered, such as reviewing financial performance whether it is in accordance with policy and is able to bring sharia commercial banks into healthier banks. Originality/value: originality Paper type: Research paper